Congenital Transmission of Infectious Bovine Rhinotracheitis (Ibr) in Cattle and Buffalo in Indonesia - ., Sudarisman (Indonesian Animal Sciences Society, 2007)
Congenital transmissions of infectious bovine rhinotracheitis (IBR) in cattle and buffalo in Indonesia have been found along time ago, primarily in animals treated with artificial insemination which semen came from the BHV-1 virus infected bull. The artificial insemination industry concerns with BHV-1 virus contamination of semen from healthy seropositive bulls with latent infections. Collection of semen from bulls maintained with a rigorous herd health program is an unlikely source of distribution of BHV-1 virus. Virus from the lesions in infected bulls can contaminate semen and causes a hazard to artificial insemination practices. Preventing the congenital transmission should be done at the artificial insemination centre through a standard procedure for semen production and the semen must come from a seronegative BHV-1 virus bull. Serological test for BHV-1 virus should be done every six months and PCR test should be conducted to the semen batch showed seropositive results and also to the bulls showed clinical signs of IBR. Virus isolation can be done from samples of suspected bulls. Bulls are potential sources of infection, thus keeping the seropositive or IBR infected bulls should be avoided. Such bulls can transmit the disease during breeding. Some female cattle can develop a latent infection that can be reactivated, and the disease can be transmitted to the male during breeding or in neonatal calves during late gestation or shortly after birth. Embryo transfer technique which is encouraged at this time is also a concern since its possibility infected with BHV-1 virus. Â Key words: Infectious bovine rhinotracheitis (IBR), semen, cattle, artificial insemination, buffalo